Microsoft Project 2010 step by step - Chatfield, Carl S., 1964-; Johnson, Timothy D., 1962- (Redmond, Wash. : Microsoft Press, 2010)
Microsoft Project 2010 offers flexibility and choice for individuals, teams, and the enterprise to effectively manage all types of work - from simple tasks to complex projects and programs.
Simple scheduling. A guided tour of Project ; Creating a task list ; Setting up resources ; Assigning resources to tasks ; Formatting and sharing your plan ; Tracking progress on tasks -- Advanced scheduling. Fine-tuning task details ; Fine-tuning resource details ; Fine-tuning assignment details ; Fine-tuning the project plan ; Organizing project details ; Tracking progress on tasks and assignments ; Viewing and reporting project status ; Getting your project back on track -- Special subjects. Applying advanced formatting and printing ; Customizing project ; Sharing project information with other programs ; Consolidating projects and resources -- Appendices. A short course in project management ; Roadmap for developing your project and project management skills ; Using the practice files if connected to Project server ; Using Microsoft Project 2010 step by step in a classroom : suggestions for instructors.
Includes index.
Keywords: Microsoft Project; Project management -- Computer programs; Microsoft Project (Computer software); Project management -- Computer software